2022
DOI: 10.1557/s43578-022-00579-1
|View full text |Cite
|
Sign up to set email alerts
|

Na uptake at TiO2 anatase surfaces under electric field control: A first-principles study

Abstract: Na-ion batteries (NIBs) are promising devices for large-scale energy-storage facilities. Nanostructured TiO2 is an efficient NIB negative electrode, showing good cycling performance and rate capability, but its activity depends on the crystalline facets exposed by anatase nanoparticles. Hence, we propose here a DFT+U study of Na+ adsorption and insertion at (101), (100) and (001)-TiO2 surfaces under the influence of external electric fields, which are simulated by adding a sawtooth-like electrostatic potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…It was also found that field polarization affects Na + uptake as well as titania electronic features, promoting redox processes within Ti sublattice. These results highlight the high‐energy (001) surface is the most active, for both directions of external fields, proving its activity to be exerted reversibly [44] …”
Section: Outcomes Of the Projectmentioning
confidence: 69%
See 3 more Smart Citations
“…It was also found that field polarization affects Na + uptake as well as titania electronic features, promoting redox processes within Ti sublattice. These results highlight the high‐energy (001) surface is the most active, for both directions of external fields, proving its activity to be exerted reversibly [44] …”
Section: Outcomes Of the Projectmentioning
confidence: 69%
“…Ab-initio computational simulations of the geometric and electronic properties of cathodes for SIBs were performed [42] and the atomic interaction between the surface of the ionic polymers and the sodium metal electrode was investigated. [43][44][45] Using a new surface slab model, the interaction between the layered Na 0.85 Li 0.17 Ni 0.21 Mn 0.64 O 2 (001) surface and the Na + ions was examined to identify the most favourable adsorption sites and the possible paths for the migration of the Na + ions on the electrode surface. The analysis of atomic partial charges and atomic magnetic moments revealed that Li has a purely structural role, while Ni and Mn actively participate in both redox processes and electronic conduction.…”
Section: Innovative Electrode Materials For Li-and Na-ion Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…By accessing the electronic structure of materials, QM methods enable both the prediction of materials' properties and the fundamental understanding of their complex mechanisms of functioning. Indeed, the latest example is represented by the DFT work of Fasulo et al [17], published in this focus issue, where electric field polarization effects on TiO 2 nanoparticles are shown to favor reversible Na uptake at the (001) surface.…”
Section: Progress In Computationsmentioning
confidence: 99%